Secretory IgA N- and O-Glycans Provide a Link between the Innate and Adaptive Immune Systems - Louise Royle; Anja Roos; David J. Harvey; Mark R. Wormald; Daniëlle Van Gijlswijk‐Janssen; Elrashdy M. Redwan; Ian A. Wilson; Mohamed R. Daha; Raymond A. Dwek; Pauline M. Rudd (2003)
Secretory IgA (SIgA) is a multi-polypeptide complex consisting of a secretory component (SC) covalently attached to dimeric IgA containing one joining (J) chain. We present the analysis of both the N- and O-glycans on the individual peptides from this complex. Based on these data, we have constructed a molecular model of SIgA1 with all its glycans, in which the Fab arms form a T shape and the SC is wrapped around the heavy chains. The O-glycan regions on the heavy (H) chains and the SC N-glycans have adhesin-binding glycan epitopes including galactose-linked β1-4 and β1-3 to GlcNAc, fucose-linked α1-3 and α1-4 to GlcNAc and α1-2 to galactose, and α2-3 and α2-6-linked sialic acids. These glycan epitopes provide SIgA with further bacteria-binding sites in addition to the four Fab-binding sites, thus enabling SIgA to participate in both innate and adaptive immunity. We also show that the N-glycans on the H chains of both SIgA1 and SIgA2 present terminal GlcNAc and mannose residues that are normally masked by SC, but that can be unmasked and recognized by mannose-binding lectin, by disrupting the SC-H chain noncovalent interactions. Secretory IgA (SIgA) is a multi-polypeptide complex consisting of a secretory component (SC) covalently attached to dimeric IgA containing one joining (J) chain. We present the analysis of both the N- and O-glycans on the individual peptides from this complex. Based on these data, we have constructed a molecular model of SIgA1 with all its glycans, in which the Fab arms form a T shape and the SC is wrapped around the heavy chains. The O-glycan regions on the heavy (H) chains and the SC N-glycans have adhesin-binding glycan epitopes including galactose-linked β1-4 and β1-3 to GlcNAc, fucose-linked α1-3 and α1-4 to GlcNAc and α1-2 to galactose, and α2-3 and α2-6-linked sialic acids. These glycan epitopes provide SIgA with further bacteria-binding sites in addition to the four Fab-binding sites, thus enabling SIgA to participate in both innate and adaptive immunity. We also show that the N-glycans on the H chains of both SIgA1 and SIgA2 present terminal GlcNAc and mannose residues that are normally masked by SC, but that can be unmasked and recognized by mannose-binding lectin, by disrupting the SC-H chain noncovalent interactions. Secretory IgA (SIgA) 1The abbreviations used are: SIgA, secretory immunoglobulin A; AxGy, complex glycan with x antennae and y galactose residues; 2AB, 2-aminobenzamide; ELISA, enzyme-linked immunosorbent assay; ESI, electrospray ionization; Fuc, fucose; Fc, fucose-linked α1-6 to core GlcNAc; Gal, galactose; GU, glucose unit(s); H chain, heavy chain; Hex, hexose; HexNAc, N-acetylhexosamine; HPLC, high performance liquid chromatography; J chain, joining chain; LC, liquid chromatography; MBL, mannose-binding lectin; MS, mass spectrometry; Neu5Ac, N-acetylneuraminic acid; NP, normal phase; pIgR, polymeric immunoglobulin receptor; SC, secretory component; MES, 4-morpholinoethanesulfonic acid.1The abbreviations used are: SIgA, secretory immunoglobulin A; AxGy, complex glycan with x antennae and y galactose residues; 2AB, 2-aminobenzamide; ELISA, enzyme-linked immunosorbent assay; ESI, electrospray ionization; Fuc, fucose; Fc, fucose-linked α1-6 to core GlcNAc; Gal, galactose; GU, glucose unit(s); H chain, heavy chain; Hex, hexose; HexNAc, N-acetylhexosamine; HPLC, high performance liquid chromatography; J chain, joining chain; LC, liquid chromatography; MBL, mannose-binding lectin; MS, mass spectrometry; Neu5Ac, N-acetylneuraminic acid; NP, normal phase; pIgR, polymeric immunoglobulin receptor; SC, secretory component; MES, 4-morpholinoethanesulfonic acid. is the major immunoglobulin responsible for protecting the mucosal surfaces against invasion by pathogens. In humans, mucosa covers a vast surface area (∼400 m3), and the body produces more SIgA each day than all other antibodies combined (66 mg kg-1 day-1) (1Kerr M.A. Biochem. J. 1990; 271: 285-296Crossref PubMed Scopus (439) Google Scholar). SIgA occurs mainly as a dimer in which the two IgA molecules are joined together via a small (16 kDa) J chain (joining chain) (2Johansen F.E. Braathen R. Brandtzaeg P. J. Immunol. 2001; 167: 5185-5192Crossref PubMed Scopus (166) Google Scholar), which is linked to the terminal cysteine of one heavy (H) chain on each IgA. The dimeric IgA with attached J chain is produced in plasma cells close to the epithelium. The epithelial cells express the polymeric immunoglobulin receptor (pIgR) that binds to dimeric IgA; this complex is then translocated across the epithelial cell. During translocation disulfide bonding occurs between the pIgR and one H chain. On reaching the mucosal surface, the (50-90-kDa) secretory component (SC) is cleaved from the pIgR transmembrane tail, and the whole IgA/J chain/SC (SIgA) complex is secreted (3Norderhaug I.N. Johansen F.E. Schjerven H. Brandtzaeg P. Crit. Rev. Immumol. 1999; 19: 481-508PubMed Google Scholar). Thus, SIgA is a multi-polypeptide complex originating from two cell types (3Norderhaug I.N. Johansen F.E. Schjerven H. Brandtzaeg P. Crit. Rev. Immumol. 1999; 19: 481-508PubMed Google Scholar). This is in contrast to serum IgA, which is predominantly monomeric and lacks the J chain and SC.There are two isotypic forms of IgA: IgA1 and IgA2. Both forms contain two conserved N-glycan sites per H chain, one at Asn263 in the Cα2 domain and one on the terminal amino acid (Asn459) of its 18-amino acid tail piece (compared with IgG, IgA has an extra 18 amino acids on the C-terminal of the H chain). There are two allotypes of IgA2, IgA2m(1) and IgA2m(2), that contain further conserved N-glycan sites: one on the Cα2 domain and one or two on the Cα1 domain respectively (1Kerr M.A. Biochem. J. 1990; 271: 285-296Crossref PubMed Scopus (439) Google Scholar) (Fig. 1). SC is highly glycosylated, it has seven N-glycan sites, and sugars contribute up to 25% of its molecular mass, whereas the J chain has only one N-glycan site (3Norderhaug I.N. Johansen F.E. Schjerven H. Brandtzaeg P. Crit. Rev. Immumol. 1999; 19: 481-508PubMed Google Scholar). In addition, IgA1 has a 23-amino acid, proline-rich hinge region with nine potential O-glycosylation sites (serine and threonine residues) of which three to five sites have been shown to be occupied in serum IgA1 (4Baenziger J. Kornfeld S. J. Biol. Chem. 1974; 249: 7270-7281Abstract Full Text PDF PubMed Google Scholar, 5Iwase H. Tanaka A. Hiki Y. Kokubo T. Ishii-Karakasa I. Kobayashi Y. Hotta K. J. Biochem. (Tokyo). 1996; 120: 393-397Crossref PubMed Scopus (50) Google Scholar, 6Mattu T.S. Pleass R.J. Willis A.C. Kilian M. Wormald M.R. Lellouch A.C. Rudd P.M. Woof J.M. Dwek R.A. J. Biol. Chem. 1998; 273: 2260-2272Abstract Full Text Full Text PDF PubMed Scopus (350) Google Scholar, 7Novak J. Tomana M. Kilian M. Coward L. Kulhavy R. Barnes S. Mestecky J. Mol. Immunol. 2000; 37: 1047-1056Crossref PubMed Scopus (59) Google Scholar). IgA2 lacks this 13-amino acid hinge region and is not O-glycosylated.A newborn child relies on passive immunity from the SIgA in its mother's milk until its own immune system has matured. The SIgA in colostrum and milk binds to microorganisms, their metabolic products and toxins, preventing their attachment to the gut epithelium and facilitating their expulsion in the feces, a process known as immune exclusion (8Lamm M.E. Annu. Rev. Microbiol. 1997; 51: 311-340Crossref PubMed Scopus (336) Google Scholar). The adhesion of many pathogenic organisms to mucosal membrane cells is mediated by adhesins on their surface. These are lectin-like receptors that can bind to complementary carbohydrate constituents expressed by the host tissues (9Sharon N. Ofek I. Glycoconj. J. 2000; 17: 659-664Crossref PubMed Scopus (182) Google Scholar). For example, S-fimbriated Escherichia coli, which causes sepsis and meningitis in newborns, can be prevented from binding to epithelial cells, independently of the antigen-binding sites, by sialylated glycans on SIgA that bind to the pathogen (10Schroten H. Stapper C. Plogmann R. Kohler H. Hacker J. Hanisch F.G. Infect. Immun. 1998; 66: 3971-3973Crossref PubMed Google Scholar). Fucose, linked α1-2 to galactose as in Lewisb and Lewisy epitopes, on SC N-glycans compete with Helicobacter pylori for binding to gastric receptors (11Falk P. Roth K.A. Boren T. Westblom T.U. Gordon J.I. Normark S. Proc. Natl. Acad. Sci. U. S. A. 1993; 90: 2035-2059Crossref PubMed Scopus (243) Google Scholar, 12Boren T. Falk P. Roth K.A. Larson G. Normark S. Science. 1993; 262: 1892-1895Crossref PubMed Scopus (989) Google Scholar). Free SC also binds to E. coli (13Wold A.E. Mestecky J. Tomana M. Kobata A. Ohbayashi H. Endo T. Eden C.S. Infect. Immun. 1990; 58: 3073-3077Crossref PubMed Google Scholar, 14de Oliveira I.R. de Araujo A.N. Bao S.N. Giugliano L.G. FEMS Microbiol. Lett. 2001; 203: 29-33Crossref PubMed Scopus (62) Google Scholar) and toxin A from Clostridium difficile (15Dallas S.D. Rolfe R.D. J. Med. Microbiol. 1998; 47: 879-888Crossref PubMed Scopus (122) Google Scholar), and both free and SIgA-bound SC interact specifically with a surface protein of Streptococcus pneumoniae (16Hammerschmidt S. Talay S.R. Brandtzaeg P. Chhatwal G.S. Mol. Microbiol. 1997; 25: 1113-1124Crossref PubMed Scopus (259) Google Scholar, 17Zhang J.R. Mostov K.E. Lamm M.E. Nanno M. Shimida S. Ohwaki M. Tuomanen E. Cell. 2000; 102: 827-837Abstract Full Text Full Text PDF PubMed Scopus (319) Google Scholar). Type 1-fimbriated E. coli express a mannose-specific lectin that binds to SIgA (13Wold A.E. Mestecky J. Tomana M. Kobata A. Ohbayashi H. Endo T. Eden C.S. Infect. Immun. 1990; 58: 3073-3077Crossref PubMed Google Scholar). This has led to an increased interest in the use of orally administered recombinant SIgA for passive immunization against virulent pathogens such as C. difficile and Neisseria meningitis (18Corthesy B. Trends. Biotechnol. 2002; 20: 65-71Abstract Full Text Full Text PDF PubMed Scopus (47) Google Scholar, 19Corthesy B. Spertini F. Biol. Chem. 1999; 380: 1251-1262Crossref PubMed Scopus (37) Google Scholar). However, accurately defining glycan structures is a prerequisite to understanding their binding properties, particularly because proteins made in different cell types are differently glycosylated, and this can have major implications when producing engineered antibodies (20Wright A. Morrison S.L. Trends. Biotechnol. 1997; 15: 26-32Abstract Full Text PDF PubMed Scopus (268) Google Scholar).In this paper we present the first total N-and O-glycan analysis of each of the different peptide chains (H, J, and SC) from the same sample of normal pooled human SIgA. Sensitive analytical procedures have enabled us to identify minor components of the glycan pool in addition to confirming the major glycan structures found by previous investigators (21Pierce-Cretel A. Debray H. Montreuil J. Spik G. Van Halbeek H. Mutsaers J.H. Vliegenthart J.F. Eur. J. Biochem. 1984; 139: 337-349Crossref PubMed Scopus (22) Google Scholar, 22Pierce-Cretel A. Decottignies J.P. Wieruszeski J.M. Strecker G. Montreuil J. Spik G. Eur. J. Biochem. 1989; 182: 457-476Crossref PubMed Scopus (44) Google Scholar, 23Pierce-Cretel A. Pamblanco M. Strecker G. Montreuil J. Spik G. Eur. J. Biochem. 1981; 114: 169-178Crossref PubMed Scopus (53) Google Scholar, 24Pierce-Cretel A. Pamblanco M. Strecker G. Montreuil J. Spik G. Dorland L. Van Halbeek H. Vliegenthart J.F. Eur. J. Biochem. 1982; 125: 383-388Crossref PubMed Scopus (27) Google Scholar, 25Mizoguchi A. Mizuochi T. Kobata A. J. Biol. Chem. 1982; 257: 9612-9621Abstract Full Text PDF PubMed Google Scholar, 26Hughes G.J. Reason A.J. Savoy L. Jaton J. Frutiger-Hughes S. Biochim. Biophys. Acta. 1999; 1434: 86-93Crossref PubMed Scopus (45) Google Scholar, 27Purkayastha S. Rao C.V. Lamm M.E. J. Biol. Chem. 1979; 254: 6583-6587Abstract Full Text PDF PubMed Google Scholar, 28Baenziger J. J. Biol. Chem. 1979; 254: 4063-4071Abstract Full Text PDF PubMed Google Scholar). The O-glycans on the H chain and the N-glycans on SC presented a wide range of epitopes for adhesin binding. Over 75% of the N-glycans on the J chain were sialylated, whereas over 66% of the N-glycans on the H chain were truncated complex structures with free terminal GlcNAcs.On the basis of these data we have constructed a molecular model of SIgA1 with its glycans attached, in which the Fab arms form a T shape and the SC is wrapped around the H chains. This model shows that glycans cover most of the SIgA1 complex with the exception of the Fab regions. Each SIgA1 molecule has several sites for binding to pathogens. In addition to the four Fab antigen-binding sites (adaptive immunity), there are two O-glycosylated regions containing up to 10 glycans per region and SC with seven N-glycans, which present a wide range of sugar epitopes capable of binding to adhesins (innate immunity).Our model of SIgA1 shows the SC wrapped around the H chains, masking the H chain N-glycans, which are truncated complex structures with free terminal GlcNAc residues. These GlcNAc residues are potential ligands for lectins such as mannose-binding lectin (MBL). MBL is a calcium-dependent serum lectin that is able to bind to d-mannose, l-fucose, GlcNAc, and N-acetylmannoseamine, recognizing two common equatorial hydroxyl groups (29Weis W.I. Drickamer K. Hendrickson W.A. Nature. 1992; 360: 127-134Crossref PubMed Scopus (847) Google Scholar). Binding of MBL to microorganisms, including viruses, bacteria, and yeast species, can induce activation of the complement system via the lectin pathway, thus leading to target opsonization. MBL represents a key component of the innate immune system, as illustrated by the increased susceptibility to infections occurring in MBL-deficient individuals (30Petersen S.V. Thiel S. Jensenius J.C. Mol. Immunol. 2001; 38: 133-149Crossref PubMed Scopus (257) Google Scholar). Recently, binding of the lectin domain of MBL to polymeric serum IgA has been reported (31Roos A. Bouwman L.H. van Gijlswijk-Janssen D.J. Faber-Krol M.C. Stahl G.L. Daha M.R. J. Immunol. 2001; 167: 2861-2868Crossref PubMed Scopus (326) Google Scholar). We show that MBL does not bind to SIgA at neutral pH, supporting the proposal that SC is masking the H chain N glycans, and that disruption the SC-IgA noncovalent interactions, by preincubation at pH 3, unmasks the H chain N-glycans, allowing MBL to bind.EXPERIMENTAL PROCEDURESSecretory IgA—;Pooled human SIgA, purified from colostrum, was obtained from Sigma. The secretory IgA complex was reduced, alkylated, and then separated into SC, J chain, H chain, and light chain by reducing SDS-PAGE (80 × 80 × 1 mm, 10% BisTris NuPAGE gel, MES SDS running buffer (Invitrogen)). The protein bands were visualized by Coomassie staining. MultiMark molecular mass standards were used (Invitrogen). Relative amounts of IgA1 and IgA2 were determined by ELISA according to Ref. 32de Fijter J.W. van den Wall Bake A.W. Braam C.A. van Es L.A. Daha M.R. J. Immunol. Methods. 1995; 187: 221-232Crossref PubMed Scopus (24) Google Scholar using normal human serum with known concentrations of IgA1 (2.1 mg/ml) and IgA2 (0.2 mg/ml) as standards.Identification of Gel Bands by Mass Spectrometry—;Coomassiestained bands were excised and in-gel digested with trypsin (sequencing grade; Roche Applied Science) as described in Ref. 33Shevchenko A. Wilm M. Vorm O. Mann M. Anal. Chem. 1996; 68: 850-858Crossref PubMed Scopus (7772) Google Scholar. The mixtures of recovered tryptic peptides were desalted by loading onto a PepMap C18 0.3 × 5 mm cartridge (LC packings; Presearch Ltd., Hitchin, UK) in water with 0.1% formic acid and then eluting with 80% acetonitrile, 0.1% formic acid at a flow of 0.2 μl min-1 directly into a hybrid quadrupole time-of-flight mass spectrometer fitted with a nanospray source (Waters-Micromass Ltd., Manchester, UK). The peptides were sequenced from fragmentation data as described (34Wilm M. Shevchenko A. Houthaeve T. Breit S. Schweigerer L. Fotsis T. Mann M. Nature. 1996; 379: 466-469Crossref PubMed Scopus (1505) Google Scholar). A BLAST search of the NCBI data base was performed using MASCOT software.Release and Fluorescent Labeling of Glycans—;N-Glycans were released from excised gel bands by in-gel digestion of the protein with peptide: N-glycosidase F (Roche Applied Science) (35Küster B. Wheeler S.F. Hunter A.P. Dwek R.A. Harvey D.J. Anal. Biochem. 1997; 250: 82-101Crossref PubMed Scopus (321) Google Scholar). Manual hydrazinolysis (36Patel T. Bruce J. Merry A. Bigge C. Wormald M. Jaques A. Parekh R. Biochemistry. 1993; 32: 679-693Crossref PubMed Scopus (342) Google Scholar, 37Royle L. Mattu T.S. Hart E. Langridge J.I. Merry A.H. Murphy N. Harvey D.J. Dwek R.A. Rudd P.M. Anal. Biochem. 2002; 304: 70-90Crossref PubMed Scopus (177) Google Scholar) was used to release O-glycans (60 ° for 6 h) from the whole SIgA complex. Released glycans were fluorescently labeled with 2-aminobenzamide (2AB) by reductive amination according to the method of Bigge et al. (38Bigge J.C. Patel T.P. Bruce J.A. Goulding P.N. Charles S.M. Parekh R.B. Anal. Biochem. 1995; 230: 229-238Crossref PubMed Scopus (722) Google Scholar) using an Oxford GlycoSciences Signal™ labeling kit (Oxford GlycoSciences, Abingdon, UK).Analysis of Glycans by High Performance Liquid Chromatography (HPLC)—;Normal phase (NP) HPLC was performed according to the low salt buffer system as previously described (39Guile G.R. Rudd P.M. Wing D.R. Prime S.B. Dwek R.A. Anal. Biochem. 1996; 240: 210-226Crossref PubMed Scopus (458) Google Scholar) using a 4.6 × 250-mm GlycoSep-N column (Oxford GlycoSciences). The system was calibrated using an external standard of hydrolyzed and 2AB-labeled glucose oligomers to create a dextran ladder. Weak anion exchange HPLC (40Guile G.R. Wong S.Y. Dwek R.A. Anal. Biochem. 1994; 222: 231-235Crossref PubMed Scopus (66) Google Scholar) was performed using a Vydac 301VHP575 7.5 × 50-mm column (Anachem Ltd., Luton, Bedfordshire, UK) according to the modified methodology (41Zamze S. Harvey D.J. Chen Y.J. Guile G.R. Dwek R.A. Wing D.R. Eur. J. Biochem. 1998; 258: 243-270Crossref PubMed Scopus (71) Google Scholar). These HPLC methods are described in detail in Ref. 37Royle L. Mattu T.S. Hart E. Langridge J.I. Merry A.H. Murphy N. Harvey D.J. Dwek R.A. Rudd P.M. Anal. Biochem. 2002; 304: 70-90Crossref PubMed Scopus (177) Google Scholar.Exoglycosidase Digestions—;Arrays of exoglycosidases were used in combination with HPLC to determine the sequence, monosaccharide type, and linkage of sugar residues as described in Ref. 37Royle L. Mattu T.S. Hart E. Langridge J.I. Merry A.H. Murphy N. Harvey D.J. Dwek R.A. Rudd P.M. Anal. Biochem. 2002; 304: 70-90Crossref PubMed Scopus (177) Google Scholar. The enzymes used were: Arthrobacter ureafaciens sialidase (EC 3.2.1.18), 1-2 units/ml; Newcastle disease virus (Hitcher B1 Strain) sialidase (EC 3.2.1.18), 0.2 unit/ml; S. pneumoniae sialidase recombinant in E. coli (EC 3.2.1.18) 1 unit/ml; bovine kidney α-fucosidase (EC 3.2.1.51), 1 unit/ml; almond meal α-fucosidase (EC 3.2.1.111), 3 milliunits/ml; bovine testes β-galactosidase (EC 3.2.1.23), 2 units/ml; S. pneumoniae β-galactosidase (EC 3.2.1.23), 80 milliunits/ml; S. pneumoniae β-N-acetylhexosaminidase (EC 3.2.1.30), 120 milliunits/ml; Jack bean β-N-acetylhexosaminidase (EC 3.2.1.30), 10 milliunits/ml; and Jack bean α-mannosidase (EC 3.2.1.24), 50 units/ml (with a second aliquot added after 12 h). All of the enzymes were from Glyko Inc. (Novato, CA).Mass Spectrometry of Glycans—;Positive ion matrix-assisted laser desorption-ionization time-of-flight mass spectra were recorded with a Micromass TofSpec 2E reflectron time-of-flight mass spectrometer (Waters-Micromass) using a saturated solution of 2,5-dihydroxybenzoic acid in acetonitrile as the matrix, as described in Refs. 37Royle L. Mattu T.S. Hart E. Langridge J.I. Merry A.H. Murphy N. Harvey D.J. Dwek R.A. Rudd P.M. Anal. Biochem. 2002; 304: 70-90Crossref PubMed Scopus (177) Google Scholar and 42Harvey D.J. Rapid Commun. Mass Spectrom. 1993; 7: 614-619Crossref PubMed Scopus (263) Google Scholar. LC-ESI-MS and MS/MS spectra were recorded from a Waters CapLC interfaced with a hybrid quadrupole time-of-flight mass spectrometer fitted with a Z-spray electrospray ion source (Waters-Micromass) and operated in positive ion mode. A 1 × 150-mm microbore NP HPLC column was packed with stationary phase material from a GlycoSep N column (Oxford GlycoSciences). The same solvents and gradient were used as for standard NP HPLC but with a flow rate of 40 μl/min (37Royle L. Mattu T.S. Hart E. Langridge J.I. Merry A.H. Murphy N. Harvey D.J. Dwek R.A. Rudd P.M. Anal. Biochem. 2002; 304: 70-90Crossref PubMed Scopus (177) Google Scholar).MBL Binding Experiments—;MBL and polymeric serum IgA were purified from human donor plasma exactly as described previously (31Roos A. Bouwman L.H. van Gijlswijk-Janssen D.J. Faber-Krol M.C. Stahl G.L. Daha M.R. J. Immunol. 2001; 167: 2861-2868Crossref PubMed Scopus (326) Google Scholar). Binding of MBL to immobilized IgA was performed by ELISA, as described (31Roos A. Bouwman L.H. van Gijlswijk-Janssen D.J. Faber-Krol M.C. Stahl G.L. Daha M.R. J. Immunol. 2001; 167: 2861-2868Crossref PubMed Scopus (326) Google Scholar). In brief, IgA was coated on ELISA plates using a carbonate buffer (pH 9.6). As a negative control, the plates were coated with purified human serum albumin (Central Laboratory of Bloodtransfusion (Sanquin), Amsterdam, the Netherlands). After each step, the plates were washed with phosphate-buffered saline containing 0.05% Tween 20. MBL was diluted in BVB++ (1.8 mm sodium 5,5-diethylbarbital, 0.2 mm 5,5-diethylbarbituric acid, 145 mm NaCl, 0.5 mm MgCl2, 1 mm CaCl2, 0.05% Tween 20, 1% bovine serum albumin, pH 7.5) and incubated in the plates for 1 h at 37 °. In some experiments, coated wells were pretreated with buffers of different pH (0.1 m glycine-HCl, pH 2.0-5.0, containing 0.15 m NaCl) for 5-60 min at 37 °, followed by washing with phosphate-buffered saline/Tween and the addition of MBL as indicated above. Furthermore, inhibition experiments were performed using 10 mm EDTA or 50 mm d-mannose, which were preincubated with MBL for 40 min at room temperature before the addition of MBL to the plate. Binding of MBL was examined using monoclonal antibody 3E7 directed against MBL (mouse IgG1, kindly provided by Dr. T. Fujita, Fukushima, Japan), conjugated to digoxygenin (Roche Applied Science), followed by horseradish peroxidase-conjugated rabbit anti-digoxygenin antibodies (Fab fragments; Roche Applied Science). Enzyme activity of horseradish peroxidase was detected using 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (from Sigma), and the A values at 415 nm were measured.Molecular Modeling—;Molecular modeling was performed on a Silicon Graphics Fuel work station using InsightII and Discover software (Accelrys, San Diego, CA). The figures were produced using the program Molscript (43Kraulis P.J. J. Appl. Crystallogr. 1991; 24: 946-950Crossref Google Scholar). Crystal structures used as the basis for modeling were obtained from the Brookhaven data base (44Berman H.M. Westbrook J. Feng Z. Gilliland G. Bhat T.N. Weissig H. Shindyalov I.N. Bourne P.E. Nucleic Acids Res. 2000; 28: 235-242Crossref PubMed Scopus (26684) Google Scholar). N- and O-glycan structures were generated using the data base of glycosidic linkage conformations (45Petrescu A.J. Petrescu S.M. Dwek R.A. Wormald M.R. Glycobiology. 1999; 9: 343-352Crossref PubMed Scopus (110) Google Scholar) and in vacuo energy minimization to relieve unfavorable steric interactions. The Asn-GlcNAc linkage conformations were based on the observed range of crystallographic values (46Imberty A. Perez S. Protein Eng. 1995; 8: 699-709Crossref PubMed Scopus (72) Google Scholar), the torsion angles around the Asn Cα-Cβ and Cβ-Cγ bonds then being adjusted to eliminate unfavorable steric interactions between the glycans and the protein surface.RESULTSDetermination of the Relative Amounts of IgA1 and IgA2 in SIgA—;The percentages of IgA1 (39%) and IgA2 (61%) in the total SIgA from pooled human colostrum were determined by ELISA (data not shown).Separation and Identification of SIgA Component Proteins—; Pooled normal human SIgA from colostrum was resolved into SC, H, L, and J chains by SDS-PAGE (Fig. 2). Tryptic peptides were sequenced to confirm the identity of the proteins in the gel bands (Table I). The J chain migrated with a higher apparent molecular mass than 16 kDa, in agreement with results by Chuang and Morrison (47Chuang P.D. Morrison S.L. J. Immunol. 1997; 158: 724-732PubMed Google Scholar).Fig. 2SIgA (7 μg/lane) was reduced, alkylated, and then run on a 10% BisTris gel. The N-glycans were released by in-gel N-glycosidase F digestion, 2AB-labeled, and run on NP HPLC. The HPLC traces are all on the same scale, so the relative size (GU) and abundance of N-glycans can be compared.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Table IIdentification of gel bands (shown inFig. 1) by nanospray-quadrupole time-of-flight-MS/MS of tryptic peptides followed by MASCOT search of NCBI data baseGel bandIdentificationAccession numberProtein covered%aPolymeric immunoglobulin receptor1363832010bIgA H chain constant regionAAC8252839cIg λ chainS2573634dImmunoglobulin J chainP015916 Open table in a new tab N-Glycan Analysis—;Fig. 2 shows the NP HPLC profiles of the pools of glycans released from the different gel bands. The glucose unit (GU) scale indicates the relative size of the glycans (the larger the GU, the larger the glycan). The N-glycans from the H chains ranged between GU 5 and 7; SC had the largest glycans (GU 6-12), whereas the J chain glycans were GU 6-9. Because there is only one glycosylation site per J chain and one J chain per SIgA, the abundance of glycans is lower; the light chain had negligible levels of N-glycosylation.The preliminary assignment of structures was made by comparing GU values with standards and confirmed by following the elution positions (measured in GU) of peaks through the different exoglycosidase arrays and by mass spectrometry (37Royle L. Mattu T.S. Hart E. Langridge J.I. Merry A.H. Murphy N. Harvey D.J. Dwek R.A. Rudd P.M. Anal. Biochem. 2002; 304: 70-90Crossref PubMed Scopus (177) Google Scholar, 48Rudd P.M. Morgan B.P. Wormald M.R. Harvey D.J. van den Berg C.W. Davis S.J. Ferguson M.A. Dwek R.A. J. Biol. Chem. 1997; 272: 7229-7244Abstract Full Text Full Text PDF PubMed Scopus (135) Google Scholar). In Tables II, III, IV, V, VI, the relative amounts of glycans in the pool released from each peptide can be found in the column headed "Undig." To detect the presence of a bisecting GlcNAc residue, both Jack bean β-N-acetylhexosaminidase and S. pneumonia β-N-acetylhexosaminidase digestions were performed. Jack bean β-N-acetylhexosaminidase does not digest glycans with bisecting GlcNAc, whereas S. pneumonia β-N-acetylhexosaminidase does digest bisected biantennary glycans but is inefficient at digesting tri- or tetra-antennary structures with GlcNAc β1-4 or 1-6 linked to mannose under the conditions used in this paper (data not shown). The presence of bisecting GlcNAc was also confirmed by tandem mass spectrometry (MS/MS).Table IIAnalysis of the N-glycans from H chainView Large Image Figure ViewerDownload Hi-res image Download (PPT) Open table in a new tab Table IIIAnalysis of the N-glycans from J chainView Large Image Figure ViewerDownload Hi-res image Download (PPT) Open table in a new tab Table IVAnalysis of the N-glycans from SCView Large Image Figure ViewerDownload Hi-res image Download (PPT) Open table in a new tab Table VAnalysis of the O-glycans from SIgA1View Large Image Figure ViewerDownload Hi-res image Download (PPT) Open table in a new tab Table VIAnalysis of the O-glycans from SIgA1View Large Image Figure ViewerDownload Hi-res image Download (PPT) Open table in a new tab H Chain N-Glycans—;Over 75% of the H chain N-glycans contain a bisecting GlcNAc, 66% contain a free terminal GlcNAc on one antenna, less than 20% of structures were fully galactosylated, less than 15% were sialylated (only α2-6 sialic acids detected), no glycans contained outer arm fucose residues, all galactose residues were β1-4-linked, about half the structures contained core fucose, and there were about 12% of oligomannose structures (Figs. 3 and 4 and Table II). The major structures were FcA2B (30%), A2B (21%), and FcA2BG1 (8%) (the notation is explained in footnote 1 of Table II). The glycans were of the biantennary complex type with a bisecting